The Anticancer Activity of Marine Sponge Cinachyrella sp. (Family Tetillidae) - Awik Puji Dyah Nurhayati; Rarastoeti Pratiwi; Subagus Wahyuono; Istriyati Istriyati; Nichole J de Voogt (IPTEK The Journal for Technology and Science, 2014)
Cinachyrella sp. marine sponge produce many kinds of secondary metabolites. The purpose of this study was to examine the cytotoxic and anti-proliferative activity of marine sponge Cinachyrella sp. The sponge was extracted with 96 % ethanol. Ethanol extract cytotoxicity assay were performed with MTT method (Microculture Tetrazolium) against to cell lines of HeLa, T47D, WiDr and Vero. The results show that of the ethanol extract were only toxic to cell lines of HeLa IC50 897.809 μg/mL but did not toxic to cell lines of T47D, WiDr and normal cell lines of Vero. Fractionation of the ethanol extract was conducted by a Vacuum Column Chromatography (VCC) and have 4 fraction that were F1, F2, F3 and F4. Cytotoxicity and cell proliferation inhibitory were tested of fraction F1, F2, F3 and F4 against cell lines of T47D. The values IC50 of F1; F2; F3 and F4 against cell lines of T47D were 82.744; 163.679; 66.522 and 333.026 μg/mL and fraction F3 concentration 31.5 µg/mL inhibits cell proliferation cell lines of T47D at 48 hours of incubation